齿轮传动多模式失效的时变可靠性分析 - 王明清; 陈作越 (Jixie Chuandong, 2011)
A model of time-variant reliability and its computation method of gear drive under multi-failure mode are presented.The time-variant model of gear strength is created by using the relationships curve between the gear fatigue lifecoefficient and the number of stress cycle.And then the reliability analysis model of gear drive is presented,in which the contact fatigue failure and blend fatigue failure are taken into account.The time-variant probabilistic formula of the contact fatigue failure and blend fatigue failure is derived by using the first order second moment method.The analytic formula of the joint failure probability density function of the two fatigue modes is derived.A numerical example is given to illustrate the presented method.